Legal protection for sea transport passengers - Romi Wahyudi; Dewi Astutty Mochtar (Jurnal Cakrawala Hukum, 2022)
In terms of transportation, safety and security issues are of particular concern. The shipping safety and security system is an important factor that must be considered and as a basis and benchmark for decision-making in determining the feasibility of shipping both in terms of facilities in the form of ships and infrastructure such as navigation systems, and the human resources involved in it. Indonesia has sovereignty over the entire Indonesian sea area, so the sea has a significant role in both the means of unifying the nation and the territory of the Republic of Indonesia, as well as the sea as an invaluable asset of the nation and the future of Indonesia. The efforts that can be made in maximizing legal protection for passengers are to improve the legal system in the shipping sector, including the substance of the provisions regarding shipping, which are further enhanced in the form of sanctions against companies, the addition of providing adequate and comfortable facilities and infrastructure for passengers, especially in the field of legal protection against losses incurred. suffered by passengers, sometimes the transportation company pays less attention to passengers who suffer losses.